A Case Series of Anterograde and Retrograde Vascular Projectile Embolization. Issue 2 (June 2018) - Chao, Jennifer; Barnard, Jeffrey; deJong, Joyce L.; Prahlow, Joseph A.
Deaths related to firearms are common within the United States, with most cases having conspicuous projectile wounds found at autopsy. Individual gunshot wounds may be perforating or penetrating. In most cases with penetrating wounds, projectiles are relatively easily found via radiography and by following the pathway on internal examination. When a projectile is not detected in the expected region, intravascular embolization of the projectile should be suspected. Embolization may be arterial or venous, as well as anterograde or retrograde. Typically, such emboli involve small caliber bullets or shot pellets. The authors present three unusual cases of intravascular projectile embolization at autopsy, one involving shotgun slug fragment embolization, one where death was delayed, and one with retrograde embolization into the liver. Acad Forensic Pathol. 2018 8(2): 392-406